2016
DOI: 10.1016/j.jsb.2016.01.013
|View full text |Cite
|
Sign up to set email alerts
|

A new structural model of Alzheimer’s Aβ42 fibrils based on electron paramagnetic resonance data and Rosetta modeling

Abstract: Brain deposition of Aβ in the form of amyloid plaques is a pathological hallmark of Alzheimer's disease. There are two major species of Aβ in the brain: Aβ42 and Aβ40. Although Aβ40 is several-fold more abundant than Aβ42 in soluble form, Aβ42 is the major component of amyloid plaques. Structural knowledge of Aβ42 fibrils is important both for understanding the process of Aβ aggregation and for designing fibril-targeting drugs. Here we report site-specific structural information of Aβ42 fibrils at 22 residue p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 50 publications
5
60
0
Order By: Relevance
“…This b1-turn-b2 motif is the core structure of Ab40 fibrils. For the structure of Ab42 fibrils, our own studies using electron paramagnetic resonance suggest that the same b1-turn-b2 motif also exists in Ab42 fibrils [17]. We also found that Ab42 fibrils contain a turn at residues 37-38 and a C-terminal b-sheet at residues 39-41, which constitute the major difference between Ab40 and Ab42 fibrils.…”
Section: Publicationsupporting
confidence: 53%
See 4 more Smart Citations
“…This b1-turn-b2 motif is the core structure of Ab40 fibrils. For the structure of Ab42 fibrils, our own studies using electron paramagnetic resonance suggest that the same b1-turn-b2 motif also exists in Ab42 fibrils [17]. We also found that Ab42 fibrils contain a turn at residues 37-38 and a C-terminal b-sheet at residues 39-41, which constitute the major difference between Ab40 and Ab42 fibrils.…”
Section: Publicationsupporting
confidence: 53%
“… mentioned that ‘polymorphic Aβ42 fibrils prepared in vitro do not seed the growth of Aβ40 fibrils’, but no data were shown. On the other hand, seven other reports concluded that Aβ42 fibrils can seed the aggregation of Aβ40, but these reports did not meet all four technical points (Table ). In terms of Aβ42 cross‐seeding, Cukalevski et al .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations